Strategi Pengembangan Usaha Rumah Batik Idola Desa Pemusiran Kabupaten Tanjung Jabung Timur - Uswatun Hasanah; Ahmad Syukron Prasaja; Fauzan Ramli (STEKOM PRESS, 2024)
Strategy is an effort to develop a company's competitive position amidst business competition. A business development strategy is an effort to conduct an analysis of regional market conditions, both internal which includes strengths and weaknesses, external conditions which include opportunities and threats that will be faced, then alternatives are taken to determine the strategy that must be implemented. The aim of this research is to determine the strategy for developing the Idol Batik House business in Pemusiran Village, East Tanjung Jabung Regency. In this research, the method used is qualitative, the data analysis method used is SWOT analysis and the data collection method uses observation and interviews. Based on research results, Batik Idola utilizes its strengths to gain opportunities by using strategies including maintaining the quality of its batik, maximizing communication technology for marketing and technology in the production sector such as electric canting to maximize production and carry out business development. And the strategy used by Batik Idola to minimize existing weaknesses and to avoid threats that come, namely by increasing promotions by utilizing promotional media according to existing funds, and also adding distribution channels such as agents, resellers or sales.